Anthropometer chair-a good ergonomic design for elementary school students / Hanani Yuhaniz … [et al.] - Yuhaniz, Hanani; Muhammed, Suhaimi; Saleh, Abdul Hamid; Seraila, Asnawi; Abu, Falah (Research Innovation Business Unit, 2014)
Anthropometrics which deals with body measurements is the foundation for any product to be ergonomic. The objective of this project is to design a measuring instrument named the Anthropometer Chair which measures the human body in a sitting position. The chair was made due to the lack of availability of such an instrument. A custom-made sitting anthropometer chair was designed and made using wood. The final design was chosen and made to measure primary school students. Anthropometrics data were then collected and any problems with the Anthropometer Chair were noted. It is apparent that most students would fit into the chair, and can be measured correctly. However, some of the bigger sized students could not be measured as the chair could not cater to students who are atypical sizes. The results of using the Anthropometer Chair are undeniably an improvement in collecting sitting measurements. The portability and ease of use of the equipment will help researchers in gathering data in many places. Nevertheless, it is recommended that the size of the Anthropometer Chair should be revised in order to measure various human body sizes.